Lico A Causes ER Stress and Apoptosis via Up-Regulating miR-144-3p in Human Lung Cancer Cell Line H292 - Chen, Gang; Ma, Yueping; Jiang, Zhe; Feng, Yuan; Han, Yueqing; Tang, Yetian; Zhang, Juan; Ni, Hui; Li, Xuezheng; Li, Ning (Frontiers in Pharmacology, 2018)
During our study on the bioactivities of natural flavonoids, we found that the total flavonoids (TF) and the main constituent of it, licochalcone A (lico A), activated unfolded protein response (UPR) and induced autophagy and thereby apoptosis in H292 cells. MicroRNAs, such as the tumor repressor mir-144-3p, were reported to be differentially expressed in lung cancer cells and were linked to ER stress, autophagy, and apoptosis. However, the underlying miRNA-based mechanism for lico A modulating proliferation, autophagy and apoptosis in lung cancer cells is elusive. In this study, we found that mir-144-3p was down-regulated in H292 cells comparing to normal embryonic lung cells WI-38, and lico A (10 μM) could increase mir-144-3p level in H292 cells. Knockdown of mir-144-3p significantly abrogated the apoptosis and proliferation-inhibiting effects of lico A, and lico A could enhance the proliferation-inhibiting effect and apoptosis induced by mir-144-3p overexpression. Moreover, overexpression mir-144-3p could induce ER stress by down-regulating Nrf2, and lico A enhanced the Nrf2 down-regulation caused by mir-144-3p overexpression. Cotransfection experiments showed that lico A potentially increased the dicing of pre-mir-144 so as to increase the mature mir-144-3p level. Interestingly, high level of lico A (40 μM) up-regulated CHOP protein, but failed to increase the downstream genes levels of CHOP, including Bim and Bcl-2 in H292 cells. Docking studies indicated that CHOP-mediated pathway was potentially blocked by high dose of lico A. Our results suggested that lico A could cause UPR, autophagy and apoptosis, and the underlying mechanism involved up-regulation of mir-144-3p, and increased lico A level would also increase the potential for lico A inhibiting CHOP-dependent apoptosis in H292 cells.